Desarrollo psicomotor en un grupo de estudiantes de 4 años de educación inicial de la Red 06 Callao - Aguinaga Espinoza, Héctor Guillermo (2012)
This simple descriptive investigation aims to describe the psychomotor level of development in a group of 4 year-old students from Institutions of initial education of the Red 06 Callao. The sample were 80 students male and female. The Test of Psychomotor Development (TEPSI) of the authors Haeussler and Marchant (1994) adapted by Aguinaga and Aguinaga (2011), assessing the overall level of psychomotor development and dimensions of motor, coordination and language, was used. The results showed that most of students rated an average level in their general psychomotor in each of its dimensions.